Anaesthetic Management of a Case of Down Syndrome with Chronic Kidney Disease Undergoing Major Orthopaedic Surgery - Naik, Sudarshan; Prahalad, Prahalad; Kate, Shreyas (Journal of Anaesthesia and Pain, 2023)
Background: Down syndrome is one of the common congenital chromosomal disorders. Renal complications in Down syndrome patients are rare but is increasing in number due to increased survival. Anaesthesia in such patients is challenging due to intellectual disability, anatomical complications and multiple comorbidities.Case: This case report describes the pre-operative evaluation and anaesthetic management of a 19 -year-old male patient with Down syndrome with hypothyroidism with Chronic Kidney Disease stage 4 who underwent open reduction internal fixation with plating for bilateral subtrochanteric fracture under general anaesthesia. It was a complicated surgery for both surgeon and anaesthetist because the patient was anaemic with significant anticipated blood loss along with fluid restriction during theÂ  perioperative period. We had major challenges like patient positioning, significant blood loss, hypotension, and early fluid overload. But an extensive preoperative evaluation, optimization prior and proper coordination we overcame the challenges.Conclusion: Major orthopaedic surgeries in patients like Down syndrome with chronic kidney disease create a major anaesthetic challenge due to expected significant blood loss, chances of fluid overload, multiple comorbidities and intellectual disability. Thorough preoperative evaluation, intraoperative monitoring as well as postoperative period is important as several complications are envisaged. So a closed group management with orthopaedic surgeon, nephrologist, anaesthesiologist, endocrinologist, nursing team is required to handle such complicated cases.